2023
DOI: 10.1109/access.2020.2987350
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-Disease Associations Prediction Based on Neural Network-Based Matrix Factorization

Abstract: Numerous experiments have demonstrated that long non-coding RNA (lncRNA) play an important role in various systems of the human body. LncRNA deletions or mutations can cause human disease. The prediction of lncRNA-disease associations is conducive to the diagnosis and prevention of complex diseases. As we all know, it is a time-consuming and expensive process to predict lncRNA-disease associations via biological experiments. However, the computation methods can effectively discover lncRNA-disease associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Recently, with the increasing research on the function of lncRNA, more biological functions have been confirmed in succession [ 3 ]. LncRNA participates in many important physiological processes, such as nerve regeneration [ 4 ], gastric cancer [ 5 ], regulation of the cell cycle [ 6 ]. Thus, exploring lncRNA function has become a hot focus in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the increasing research on the function of lncRNA, more biological functions have been confirmed in succession [ 3 ]. LncRNA participates in many important physiological processes, such as nerve regeneration [ 4 ], gastric cancer [ 5 ], regulation of the cell cycle [ 6 ]. Thus, exploring lncRNA function has become a hot focus in recent years.…”
Section: Introductionmentioning
confidence: 99%